2021
DOI: 10.3389/fnhum.2021.739754
|View full text |Cite
|
Sign up to set email alerts
|

Reported Hearing Loss in Alzheimer’s Disease Is Associated With Loss of Brainstem and Cerebellar Volume

Abstract: Multiple epidemiological studies have revealed an association between presbycusis and Alzheimer’s Disease (AD). Unfortunately, the neurobiological underpinnings of this relationship are not clear. It is possible that the two disorders share a common, as yet unidentified, risk factor, or that hearing loss may independently accelerate AD pathology. Here, we examined the relationship between reported hearing loss and brain volumes in normal, mild cognitive impairment (MCI) and AD subjects using a publicly availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Strikingly, the poorer cognitive performance in MMC residents was associated with caudate and left orbital gyrus atrophy in keeping with orbital frontal cortex connections with regions processing visual, spatial, emotional information and social cognition, PFCcaudate brain wiring, and caudate functions affecting learning, memory, reward and motivation [69][70][71][72][73][74]. The current findings are not unexpected, i.e., the cerebellar atrophy is significant and could have a clinical counterpart in gait and equilibrium abnormalities described by our group in young MMC urbanites [75], cognitive deficits [16,57], the association between hearing loss and decreased brainstem and cerebellar volumes in AD cases [76], and gait and cognitive abnormalities associated with regional cerebellar atrophy in elderly fallers [77]. Cerebellar atrophy is particularly intriguing in view of our published cerebellar higher concentrations of magnetite (estimated from their saturation remanent magnetisation (SIRM) values) in MMC young forensic cases [2] and the recent description of regional cerebellar hypermetabolism in AD [78].…”
Section: Discussionsupporting
confidence: 64%
“…Strikingly, the poorer cognitive performance in MMC residents was associated with caudate and left orbital gyrus atrophy in keeping with orbital frontal cortex connections with regions processing visual, spatial, emotional information and social cognition, PFCcaudate brain wiring, and caudate functions affecting learning, memory, reward and motivation [69][70][71][72][73][74]. The current findings are not unexpected, i.e., the cerebellar atrophy is significant and could have a clinical counterpart in gait and equilibrium abnormalities described by our group in young MMC urbanites [75], cognitive deficits [16,57], the association between hearing loss and decreased brainstem and cerebellar volumes in AD cases [76], and gait and cognitive abnormalities associated with regional cerebellar atrophy in elderly fallers [77]. Cerebellar atrophy is particularly intriguing in view of our published cerebellar higher concentrations of magnetite (estimated from their saturation remanent magnetisation (SIRM) values) in MMC young forensic cases [2] and the recent description of regional cerebellar hypermetabolism in AD [78].…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies suggest that hearing loss causes brain changes that raise the risk for AD. Individuals with moderate to severe hearing loss are up to five times as likely to develop AD-associated dementia, though more research is needed to determine the exact connection between sound, hearing loss, and AD [ 134 , 135 , 136 ].…”
Section: Multiple Strategies To Optimize Brain Healthmentioning
confidence: 99%
“…This hypothesis is mainly based on the ability of cerebral hypoperfusion, caused by cortical microinfarcts, to exacerbate a cognitive decline in AD [ 24 ]. On the other hand, many epidemiological studies have shown the link between ARHL and AD associated with the loss of the brainstem and cerebellar volume [ 25 ]. Moreover, this biomarker has been established for various cardiovascular and cerebrovascular pathologies, including congenital heart disease, stroke and carotid stenosis [ 24 , 26 , 27 ].…”
Section: Introduction: Alzheimer’s Disease—etiology and Pathophysiologymentioning
confidence: 99%